Presentation - Editores (Farol, 2023)
We are pleased to publish Revista Farol number 27, with the thematic dossier covering articles that deal with contemporary art and the diversity of expressions that direct the focus and discussion on “processes, notebooks, poetic sketches”. The interdisciplinary aspect of the articles presented is noticeable, enabling many possible readings such as historical, material, artistic, among others. [...]